PENGARUH KOMPENSASI, KEPEMIMPINAN, STIMULASI SOSIAL DAN KERJA SERTA KONDISI KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI RUMAH SAKIT BAPTIS BATU - Sriwati Sriwati (JURNAL DIMENSI, 2016)
This study aims to 1) analyze the effect of variable compensation, leadership style, social stimulation and work, and working conditions on employee job satisfaction at Baptist Hospital Batu and 2) to analyze which variables among these factors are the dominant influence on employee job satisfaction Baptist Hospital in BatuThe results showed that the variable compensation, leadership style, social stimulation and work, and working conditions have a significant effect on employee job satisfaction at Baptist Hospital Batu. So suitability salary with the duties and responsibilities, leadership style conformity with the will of employees, high social stimulation and employment and good working conditions will lead to increased job satisfaction of employees at Baptist Hospital Batu.Compensation is an important variable dominant influence on employee job satisfaction at Baptist Hospital Batu, thereby achieving job satisfaction is determined more by the high compensation in the form of conformity salaries received by employees with job responsibilities, as well as the amount of salary received as compared with the type and responsibilities same responsibilities elsewhere.